THE RELATION BETWEEN GUARANTEE AND RELATED INSTITUTES OF COMMERCIAL LAW - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
This paper analyses the surety contract and institutes of the Commercial Law arising from this personal asset to secure claims. The roots of the institute of surety may be traced to the Law of the Twelve Tables. Assets to secure claims are important instruments of developing legal transactions and establishing legal security in the economy. A comparative approach to institutes which have evolved from the surety contract indicate the potentials of new assets to secure claims on the one, and possible courses of further development of these legal affairs on the other hand.